CONSTRUCTIONS OF SOCIAL REALITY NOVEL KERUMUNAN TERAKHIR BY OKKY MADASARI: STUDY OF SOCIAL CONSTRUCTION THEORY BY PETER L. BERGER AND THOMAS LUCKMANN - Arief, Nurul Fakhriyah (Media Inovasi Pendidikan dan Publikasi, 2025)
This research aims to describe the social reality and social construction process in the novel Kerumunan Terakhir by Okky Madasari using Berger and Luckmann's social construction theory. This type of research is qualitative descriptive by analyzing social reality. The source of research data is the novel The Last Crowd by Okky Madasari in 2016. The data collection techniques used are reading, recording, and documentation techniques. The results of the study explain that social inequality in the novel The Last Crowd, namely in the form of inequality in education, employment, and kinship conflicts is a social reality that depicts injustice in the social system. The inequality that occurred eventually caused various kinds of conflicts in the characters. The results of social construction research are divided into three. First, the process of externalization, the social inequality in this novel was initially formed through repeated actions carried out by the characters as individuals in a community group. Second, the process of objectification, after these actions become habits, the characters begin to see actions or behaviors as natural or as if they are right and cannot be changed, so they are considered objective reality. Third, the process of internalization, at this stage figures as individuals in society begin to accept this social inequality as part of their identity and environment.